Brahms' Piano Concerto No. 2, op. 83: Analytical and Contextual Studies - Horton, Julian (Leuven Peeters, 2017)
This book offers a detailed analytical study of Brahms' Piano Concerto No. 2, Op. 83. It develops a theoretical model for analyzing nineteenth-century instrumental forms, which elucidates Op. 83 in the context of Brahms' concerted works, their precedents in the broader intertextual network of post-classical piano concerti, and their subsequent influence on concerti from Reger to Schoenberg.
Includes bibliographical references (pages 351-360) and index.
Keywords: Brahms, Johannes -- 1833-1897; Musical analysis; Concerto; Piano; Music history